PENGARUH PERBANDINGAN TERIGU DENGAN TEPUNG KECAMBAH KACANG TUNGGAK (Vigna unguiculata, (L.) Walp) TERHADAP KARAKTERISTIK COOKIES - Winata, I Ketut Triya; Wisaniyasa, Ni Wayan; Ina, Putu Timur (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 7 No 3 (2018): Jurnal ITEPA, 2018)
The purpose of this research was to know the effect of comparison wheat flour with cowpea sprout flour to the characteristics of cookies and to know the right comparison between wheat flour with cowpea sprout flour that was able to produce cookies with the best characteristics. The experimental design used Completely Randomized Design with the treatment comparison of wheat flour and cowpea sprout flour consisting of 6 levels: 100%:0%; 90%:10%; 80%:20%; 70%:30%; 60%:40%; 50%:50%. The treatment was repeated 3 times to obtain 18 units of experiment. The data obtained were analyzed by ANOVA and if the treatment had an effect on the variable then continued with Duncan test. The comparison of wheat flour with cowpea sprout flour significantly affected the content of water, ash, fat, protein, carbohydrate, coarse fiber, color, aroma, texture, taste as well overall acceptance of cookies. Comparison of 80% wheat flour:20% cowpea sprout flour had the best characteristics of cookies the content of water 2.41%, ash 1.26%, fat 23.44%, protein 11.38%, carbohydrate 61.51%, crude fiber 8.94%, the color, flavor, texture, taste, overall acceptance liked, had brown color and very crunchy texture.